2020
DOI: 10.1371/journal.pone.0227667
|View full text |Cite
|
Sign up to set email alerts
|

Redefining transcriptional regulation of the APOE gene and its association with Alzheimer’s disease

Abstract: The apolipoprotein E gene (APOE) is the strongest genetic risk factor for late-onset Alzheimer's disease (AD), yet the expression of APOE is not clearly understood. For example, it is unclear whether AD patients have elevated or decreased APOE expression or why the correlation levels of APOE RNA and the ApoE protein differ across studies. Likewise, APOE has a single CpG island (CGI) that overlaps with its 3'-exon, and this CGI's effect is unknown. We previously reported that the APOE CGI is highly methylated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…After age 80, AD brains only had lower expression in NECTIN2 and CLPTM1. These findings confirm associations of elevated APOE mRNA in AD brains,41,42 but indicate a need for a more detailed analysis of brain regions by age.…”
supporting
confidence: 74%
“…After age 80, AD brains only had lower expression in NECTIN2 and CLPTM1. These findings confirm associations of elevated APOE mRNA in AD brains,41,42 but indicate a need for a more detailed analysis of brain regions by age.…”
supporting
confidence: 74%
“…DNA methylation of several specific genes has been investigated using candidate gene approach, with APOE being the most commonly studied gene. So far, inconsistent data have been reported, with DNA methylation being decreased in AD [ 39 , 40 , 41 , 42 ], while some studies found no differences in DNA methylation levels [ 43 , 44 ]. Additional genes of interest have been studied as well, including genes coding for brain-derived neurotrophic factor ( BDNF ) [ 45 ], glycogen synthase kinase 3 beta ( GSK3β) [ 46 ], triggering receptor expressed on myeloid cells 2 ( TREM2 ) [ 47 ], and ankyrin 1 ( ANK1 ) [ 48 ].…”
Section: Epigenetic Alterations In Alzheimer’s Diseasementioning
confidence: 99%
“…Increased TOMM40 RNA transcription in AD brains could be a consequence of prolonged mitochondrial dysfunction, which triggers a feedback response to upregulate structural proteins (e.g., TOM40) to compensate for the compromised mitochondrial function. The upregulated TOMM40 RNA in AD brains has the same trend as the upregulation of APOE mRNA in AD brains compared to control [40]. The consistent upregulation of both TOMM40 and APOE in AD brains makes the concept of co-regulation of these genes through the same topological associating domain even more appealing.…”
Section: Discussionmentioning
confidence: 88%
“…RT-qPCR assays were performed as previously reported [40]. Briefly, a fixed reversetranscribed cDNA input (5 ng) was amplified using TaqMan assays or SYBR PCR assays in a QuantStudio 5 (Applied Biosystems, Thermo Fisher).…”
Section: Reverse Transcriptase (Rt) Reaction and Quantitative Pcr (Qpcr) Assaymentioning
confidence: 99%